2016
DOI: 10.4054/demres.2016.35.19
|View full text |Cite
|
Sign up to set email alerts
|

Differences by union status in health and mortality at older ages: Results for 16 European countries

Abstract: BACKGROUNDMarried people live longer than the unmarried; micro-level research indicates that they enjoy better health. Macro-level research does not combine mortality, marital status, and health. OBJECTIVEWe provide international comparisons of healthy and unhealthy life years at ages 50 and higher combining mortality, marital status, and health. METHODSWe examine differences in healthy and unhealthy life years for married and cohabiting (i.e., partnered) and for single men and women and break these down into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…A recent study concluded that mortality, attributable to lower levels of completed education, is comparable in magnitude to mortality attributable to individuals being current rather than former smokers and the association between education and mortality could be causal [16]. Likewise, it is well known that widowers have higher mortality rates than married people [42] and that married people have a longer life expectancy compared with unmarried persons [15,34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study concluded that mortality, attributable to lower levels of completed education, is comparable in magnitude to mortality attributable to individuals being current rather than former smokers and the association between education and mortality could be causal [16]. Likewise, it is well known that widowers have higher mortality rates than married people [42] and that married people have a longer life expectancy compared with unmarried persons [15,34].…”
Section: Discussionmentioning
confidence: 99%
“…Marital status in general, and being divorced/separated in particular, is linked to disease, disability and mortality. The evidence is not new (Berkson 1962;Gove 1973;Zick and Smith 1991), but as the rate of divorce/separation remains high, its association with health has attracted substantial attention (Hughes and Waite 2009;Arcaleni 2012;Grundy and Tomassini 2010;Zhang and Hayward 2006;Pienta et al 2000;Tamborini et al 2016;Ploubidis et al 2015;Robards et al 2012;Shor et al 2012;Philipov and Scherbov 2016). With specific regard to mental health, studies have shown that separations are associated with more depression, poorer selfperceived health and greater unhappiness or unhealthy behaviors, with different symptoms for men and women (Williams 2003;Strohschein et al 2005;Gardner and Oswald 2006;Marks and Lambert 1998;Simon 2002;Williams and Dunne-Bryant 2006;Scott et al 2010).…”
Section: Partnership Status Union Dissolution and Mental Healthmentioning
confidence: 99%
“…Rezultati analize napravljene još polovinom 19. veka pokazali su da osobe u braku žive duže od ostalih, i ovaj pozitivan efekat braka na morbiditet i mortalitet supružnika, i to naročito muškaraca, potvrđen je i u mnogim kasnijim istraživanjima (Philipov, Scherbov, 2016). Posle smrti partnera, većina obudovelih ljudi se prilagodi novoj situaciji, i to bez stručne pomoći.…”
Section: Uvodunclassified